Pengaruh Kualitas Produk dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan pada Pedagang Kaki Lima di Universitas Slamet Riyadi Surakarta - Aisyah Febriana Nur Baity; Anik Indarwati; Elyn Januar Purbaningrum; Marjam Desma Rahadhini (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
This research aims to analyze the influence of product quality and service quality on customer satisfaction at street vendors at Slamet Riyadi University, Surakarta. In an era of increasingly fierce competition, product and service quality is a key factor in maintaining and increasing customer satisfaction. The research method used is quantitative with a survey approach. Data was collected through questionnaires distributed to street vendor customers in the campus area. Data analysis was carried out using multiple linear regression to see the influence of the two independent variables on customer satisfaction. The research results show that product quality and service quality significantly influence customer satisfaction. The implication of this research is that street vendors need to improve the quality of their products and services to increase customer satisfaction and maintain the sustainability of their business.